La oferta laboral en el cantón Valencia y el impacto en el crecimiento económico durante el primer semestre del año 2012 - Mera Valle, Yesica Arleni (2015)
This thesis entitled "The labor supply in the canton Valencia and impact on economic growth during the first half of 2012", has the following objectives: Identify the characteristics of the existing workforce in the canton Valencia, establish sectors the economy employing workers Cantón Valencia, determine the impact of economic growth in the canton Valencia because of the labor supply. This research was taken as scientific reference criteria other authors who discuss the subject matter in this way take concepts, approaches, theories.The research developed used methods, techniques and types of research in this way to achieve the objectives. The results obtained allowed to know that among the characteristics of the workforce of Valencia Canton that could be identified through this study found that 68.86% are male and 31.14% female, 27 09% have an age ranging from 31 to 35, while 53.67% has the degree having studied through high school and 31.14% work in agriculture, sectors of the economy employ workers Canton Valencia in accordance with the results obtained through research carried out are, the agricultural sector with 68.37%, followed by the commercial sector with 19.39%, the service sector with 9.18 %, and the industrial sector with 3.06% and the economic impact that generated the companies Valencia Canton is satisfactory, since in the last year the inhabitants have witnessed the establishment of new institutions, which also provide employment for at least ten people in most cases, meet the social, pay their employees’ salaries and have monthly sales growth of 11% to 20%.